مستوى الضغوط المهنية لدى عمال تعاونية الحبوب والبقول الجافة لولاية المسيلة - دهمش سميرة; بالقاسمي محمد الازهر (University of Eloued جامعة الوادي, 2024)
Abstract : This study aimed to reveal the level of occupational stress according to its dimensions (organizational injustice, retaliatory behavior) among a sample of workers from the dry grains and legumes cooperative in the state of M’sila. To achieve the objectives of the study, a descriptive approach was used, and an occupational stress questionnaire was applied to a sample of (97) workers. One of the workers of the dry grains and legumes cooperative in the state of M’sila. After processing the data, the study found a high level of occupational pressure among the study sample in each of its dimensions (organizational injustice, retaliatory behavior). This proves that organizational injustice is a source of occupational pressure, and retaliatory behavior is the result of the feeling of organizational injustice among grain cooperative workers. and dry legumes. These results have been discussed in light of the results of previous studies. هدفت هذه الدراسة إلى الكشف عن مستوى الضغوط المهنية وفق أبعادها (الظلم التنظيمي، السلوك الانتقامي) لدى عينة من عمال تعاونية الحبوب والبقول الجافة لولاية المسيلة، ولتحقيق أهداف الدراسة تم استخدام المنهج الوصفي، كما تم تطبيق استبيان الضغوط المهنية على عينة قوامها (97) عامل من عمال تعاونية الحبوب والبقول الجافة لولاية المسيلة. بعد معالجة البيانات توصلت الدراسة إلى وجود مستوى مرتفع في الضغوط المهنية لدى عينة الدراسة في كل من أبعادها (الظلم التنظيمي، السلوك الانتقامي)، وهذا يثبت أن الظلم التنظيمي يعد مصدرا من مصادر الضغوط المهنية، والسلوك الانتقامي هو محصلة الشعور بالظلم التنظيمي لدى عمال تعاونية الحبوب والبقول الجافة، وقد تم مناقشة هذه النتائج في ضوء نتائج الدراسات السابقة.
دراسة ميدانية
Keywords: الضغوط المهنية; الظلم التنظيمي; السلوك الانتقامي; Professional pressures; Organizational injustice; Vindictive behavior